PEMBUATAN APLIKASI SISTEM INFORMASI AKUNTANSI PADA PT. SARANA AGUNG SEJAHTERA - William Onnyxiforus Purnomo; Silvia Rostianingsih; Christian Christian (Jurnal Infra, 2016)
PT. Sarana Agung Sejahtera is a company that sold AC sparepart and AC service. This company wish to develop a new system, because had a difficulty in dealing with administrative issues because its operation is still manual, e.g. the sale and purchase transactions, preparing reports and other expenditures problem. Thus allow for errors in the calculation of sales and purchases and this can be troublesome if carried every day.Based on the problem faced by PT. Sarana Agung Sejahtera, application is made to support them. The application can process purchasing, sales order, selling, stock opname, debit and credit payment. To design the DFD of the new applications Microsoft Visio was used, and ERD application use Power Designer 15.3. This application was made using Code Igniter Framework and PostgreSQL as the database storage.The result of the application showed that this application can take notes of purchasing transactions and sales can be done according to the structure and computerize and also complemented with stock card using First In First Out (FIFO) method. Otherwise, with this application, owner can know some reports, e.g. stock card, general journal, purchasing journal, sales journal, stock position report, service report, employees report, customer reminder report, balance sheet, and income statement. This program help the transaction process with backdate feature which allows owner insert the transactions from the past time.